Gastrointestinal lymphomas: Pattern of distribution and histological subtypes: 10 years experience in a tertiary centre in South India - Neeraj Arora; Marie Therese Manipadam; Anna Pulimood; B S Ramakrishna; Ashok Chacko; Susy S Kurian; Sheila Nair (Wolters Kluwer Medknow Publications, 2011)
Background and Aim: Gastrointestinal tract (GIT) is one of the major sites of extra-nodal lymphomas constituting 10-15% of all non-Hodgkin's lymphoma cases and about 30-40% of extra-nodal lymphomas. Considerable variation exists in the literature with respect to incidence of the various histological subtypes and sites of involvement. This study was undertaken to ascertain the anatomic distribution, histological subtypes and sites of all GIT lymphomas presenting to a tertiary referral hospital in southern India. Materials and Methods: The histological material of 361 patients over a period of 10 years (2001-2010), with histopathological diagnosis of lymphoma involving the GIT (both primary and secondary), was analyzed retrospectively. All lymphomas were reclassified according to the World Health Organization 2008 classification. Results: These 361 cases include 336 primary and 25 cases of lymphomas, where the involvement was secondary. Primary lymphomas consisted of 267 males (79.64%) and 68 females (20.24%) with a male:female ratio of 3.93:1. The mean age was 45 years (range 3-88). Diffuse large B-cell lymphoma (DLBCL) was the commonest subtype (222 cases; 66.71%), followed by low-grade marginal zone lymphoma of the mucosa associated lymphoid tissue (MALT) type (34 cases; 10.12%) and Burkitt's lymphoma (35 cases; 10.48%). The commonest site was stomach (180 cases; 53.57%), followed by small intestine (79 cases; 23.51%) and large intestine (68 cases; 20.23%), respectively. There were some uncommon types of GIT lymphomas documented during the study. Conclusion: In this largest retrospective single centre study from India, we establish that the pattern of distribution of primary GIT lymphomas (PGLs) in India is similar to the western literature in that the stomach is the commonest site of PGL and DLBCL is the commonest histological subtype. Immunoproliferative small intestinal disease cases were seen in this study, which is uncommon in the west.